PENGARUH PENGEMBANGAN KARIR DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PT. UNGGUL PAWENANG SENTOSA - Fitriana Nurul Falah; Fajar Cahyo Utomo (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
To achieve an optimal work result, the company must improve the career development and compensation system in order to support the performance of employee in the company. This research was conducted to determine whether there is an effect of career development and compensation on employee performance either simultaneously or partially at PT. Unggul Pawenang Sentosa. The study was conducted on 75 respondents to employees of PT. Unggul Pawenang Sentosa. The results of tests conducted, it was found that Career Development and Compensation simultaneously had a significant effect on employee performance. In addition, Career Development and Compensation partially also have a significant effect on employee performance.